2021
DOI: 10.31228/osf.io/xd45c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Code Mixing and Code Switching in the Efl Classroom Interaction

Abstract: This research aims at finding out code mixing and code switching in the classroom interaction in terms of the teacher talk and the student talk at SMP Negeri 2 Parepare. In detail, this research aims to identify (1) the teacher talk particularly the type token ratio, the mean length of utterance as formal features, question, feedback and correction as interactional features, (2) the students talk particularly response to question and ask question as well as the students’ preference towards the use of code mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…76 However, Meristika's research found that the second common type of code switching was tag code switching. 77 Thomas found that the lecturer employed tag switching in their speech especially to quote or use the Indonesian or Javanese terms and tag switching rarely happened in this study since Indonesians do not tend to use the tag in their speech. 78 It can be seen that tag code switching was rarely used by teachers, lecturers, students in communication.…”
Section: ) Tag Code Switchingmentioning
confidence: 67%
“…76 However, Meristika's research found that the second common type of code switching was tag code switching. 77 Thomas found that the lecturer employed tag switching in their speech especially to quote or use the Indonesian or Javanese terms and tag switching rarely happened in this study since Indonesians do not tend to use the tag in their speech. 78 It can be seen that tag code switching was rarely used by teachers, lecturers, students in communication.…”
Section: ) Tag Code Switchingmentioning
confidence: 67%
“…When collecting relevant data for this research, four SLA classes from IBDP are recorded and partially transcribed, each class lasts for 40-50 minutes in a natural or near-natural environment. The CM ratio (CMR) is calculated for each selected part in the SLA classes, the quotient of the code-mixed words, which is the embedded language, English, and the total words occurred, the combination of matrix language and embedded language, that is, Chinese and English [10]. Through discourse analysis, the researcher aims to find out how frequently CM is used in SLA classes and what patterns of the linguistic codes are.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction between the teacher and students can be in the form of the teacher giving explanations, giving questions, responding to answers from students, providing motivation, praising and joking, while student responses can be in the form of answering questions from the teacher and giving opinions. (Asrifan, 2021) His research stated that studying speech in teaching and the learning process in class is an exciting topic. Therefore, the teacher has the challenge of presenting the topic of learning material excitingly so that students can feel comfortable learning English and easily understand the material presented by the teacher.…”
Section: Classroom Interactionsmentioning
confidence: 99%